Pelvic Floor Muscle Strengthening in Antenatal Period Among Primigravida Cases at Jorhat, Assam - Bandita Goswami; Ankur Jyoti Bora; Ankita Kalita (International Journal of Midwifery Nursing And Practices, 2025)
Aim: The study aimed to evaluate the effectiveness of pelvic floor muscle (PFM) strengthening exercises during the antenatal period among primigravida women in Jorhat, Assam, with a focus on improving pelvic floor muscle strength and its impact on pregnancy outcomes. Purpose: To assess whether pelvic floor muscle exercises (specifically Kegel exercises) can enhance PFM strength in pregnant women, using the Modified Oxford Grading Scale (MOS), and to compare these effects with a control group receiving standard antenatal care without specific exercises. Methodology: This case-control study was carried out at Jorhat Medical College and Hospital (JMCH) in Assam. A total of 14 primigravida women aged 20–30 years, with gestational ages between 20 and 24 weeks, were recruited and divided into two groups: Group A (experimental) and Group B (control). Group A engaged in daily Kegel exercises for 12 weeks, while Group B received routine antenatal care without specific exercises. PFM strength was evaluated through vaginal palpation and the Modified Oxford Grading Scale (MOS) at both the beginning and conclusion of the study. Data were analyzed using independent and paired t-tests, with statistical significance determined at p<0.05. Results: The mean age of participants in Group A was 22.14 years (SD=1.95), and in Group B, 25.00 years (SD=3.16). Pre-intervention PFM strength (Pre_1) was comparable between the two groups (p=0.718). Post-intervention scores (Post_1) showed significant improvement in Group A (mean Post_1 score of 4.29) compared to Group B (mean Post_1 score of 2.57), with a statistically significant difference between groups (p<0.001). Within Group A, a significant increase in PFM strength was observed post-intervention (p=0.002), while Group B showed no significant change (p=0.356). Conclusion: Pelvic floor muscle strengthening exercises, particularly Kegel exercises, performed during the antenatal period, significantly improved pelvic floor muscle strength in primigravida women. These findings suggest that incorporating PFM exercises into antenatal care can have positive outcomes on maternal health. Further research with larger sample sizes is recommended to validate these results.
Keywords: Modified Oxford Grading Scale (MOS); Pelvic floor muscles (PFM); antenatal exercises; kegel exercises; pregnancy outcomes